Examination of an Office Building’s Energy-Producing Opportunities Using the Temperature Frequency Curve - Reho, Sándor (International Journal of Engineering and Management Sciences, 2017)
In our study we would like to choose the energy generating system for a business center in Mátészalka. The system will cover the heating energy demand of shops and offices of the building. The heat demand of the building was calculated by a computer program. The energy demand was calculated with help of the Temperature Frequency Graph. In our study we choose bolilers and heat-pumps. We compared their operating costs.